The Effects of Absent or Reversed End-diastolic Umbilical Artery Doppler Flow Velocity - Kuo-Gon Wang; Chen-Yu Chen; Yi-Yung Chen (Elsevier, 2009)
Abnormal umbilical artery flow with absent or reversed end-diastolic velocity (AREDV) during pregnancy is a strong indication of placental insufficiency. When AREDV occurs prenatally, a close follow-up or expeditious delivery should be contemplated. AREDV in the umbilical artery is associated with intraventricular hemorrhage, bronchopulmonary dysplasia, and perinatal mortality. It may be associated with respiratory distress syndrome, necrotizing enterocolitis, and long-term neurodevelopmental impairment. Available data suggest that women with high-risk pregnancies, such as preeclampsia, gestational hypertension and intrauterine growth restriction, should be evaluated with umbilical artery Doppler velocimetry to reduce the possibility of perinatal mortality and morbidity.